THE EFFECTIVENESS OF USING GRAPHIC ORGANIZER CONCEPT ON STUDENTS’ READING SKILL - Sri Lestari; Bella Trivanisa (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
The aim of this research is to determine the effect of the implementation of the Graphic Organizer Concept on students’ reading skills. The method used for this study is Quasi Experimental Design with Pre-Experimental design type one-group pretest-posttest design. The total subject of this study is 15 of Primary Education Department second semester students. The Data collection techniques were carried out by tests. Test the validity of using Product Moment test while the reliability test uses Alpha, the data analysis technique uses the Kolmogorov-smirnov test with the help of the SPSS for windows program to test normality, and the t-test to test the hypothesis. Based on the research, there is an influence on the application of the Graphic Organizer Concept model, this is evidenced by the normality test results of data analysis obtained by the pretest significance of 0.134 0.05 and the posttest significance of 0.118 0.05. In the hypothesis test used the t-test, the results of the analysis of the t-test obtained t count (27,730) t table (2,131). Because t count t table then Ho is rejected and H1 is accepted. It means that graphic organizer concept affects the ability to read. The conclusion of this study is that the Graphic Organizer Concept learning model influences reading skills.